Comparison of Analysis Results pf pH, TSS, COD and Ammonia in Industry Wastewater with Sparing and SNI Methods - Dessy Nur Indryastuti; Ani Iryani; Muhammad Fathurrahman (Helium: Journal of Science and Applied Chemistry, 2022)
Sparing is a development of sensor technology to monitoring wastewater quality continuously and online, so it can be done in real time. Wastewater quality monitoring carried out in the laboratory using the SNI method still has several drawbacks, including large analysis costs, long analysis time and the use of chemicals that are not environmentally friendly. This study aims to determine the differences in the results of the analysis of the Sparing method with SNI on the parameters of pH, TSS, COD, and ammonia in the EWTP wastewater of PT "X" using statistical processing through the F-test and T-test. The research stages include sampling, sample storage and analysis in the laboratory. Based on the results of the study, it can be concluded that the differences in the method of Sparing analysis and SNI are not significantly different to the pH parameters in the measurement range 6.77 - 6.88; TSS in the measurement range 9.486 - 12.343 mg/L; COD in the measurement range of 55.402 - 59.274 mg/L and ammonia in the measurement range of 0.368 - 0.405 mg/L. This proves that the Sparing method can replace the SNI method for routinely monitoring the quality of EWTP wastewater of PT "X".